1995
DOI: 10.1680/iwtme.1995.27390
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Oxygen Content Downstream of Weirs, Spillways and Waterways.

Abstract: At hydraulic structures (e.g. weirs, spillways), air-water transfer of atmospheric gases (e.g. oxygen) occurs by self-aeration along the chute and by flow aeration in the hydraulic jump at the downstream end of the structure. In this paper, experimental data are re-analysed and compared with a numerical method to predict the free-surface aeration. Aeration at hydraulic jumps is also examined and compared with existing correlations. Calculations of free-surface aeration and empirical correlations for hydraulic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…This result is consistent with previous studies (Chanson, 1995;Richard et al, 2005) that demonstrated that low flows had higher waterfall, facilitating the flow to plunge into the water body. At low discharges, breakup of the jet is observed as drop height increases.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is consistent with previous studies (Chanson, 1995;Richard et al, 2005) that demonstrated that low flows had higher waterfall, facilitating the flow to plunge into the water body. At low discharges, breakup of the jet is observed as drop height increases.…”
Section: Discussionsupporting
confidence: 93%
“…time of the air-water exchange (Chanson, 1995;EPRI, 2002;Emiroglu & Baylar, 2006). Moreover, to obtain an unbiased estimate of the intrinsic efficiency of the devices, an assessment of the contribution of flow stretches between the devices and the downstream measurement points should have been made and it would have been better to test the structure under the entire range of upstream conditions (0 to 100% of upstream DO saturations and low to very high CH 4 saturations); which has not been possible to test for the Aeration Weir for instance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (4) is reported on figure 4. Although equation (4) is a very crude approximation, it is interesting to note the similarity of shape between the data and equation (4) Altogether the present study suggests that previous calculations of air-water interface area and air-water gas transfer (CHANSON 1994(CHANSON ,1995 are some form of reasonable approximation. H.…”
Section: Comparison With An Air-water Interface Area Modelsupporting
confidence: 65%
“…WOOD 1991, CHANSON 1994, there is little information on the air-water interface area and bubble size distributions within the flow. WILHELMS and GULLIVER (1989) and CHANSON (1995) discussed the air-water gas transfer process. GULLIVER et al (1990) and CHANSON (1994) attempted to derive bubble size predictions.…”
Section: Bibliographymentioning
confidence: 99%